Hak dan Kewajiban Suami Istri Perspektif Hukum Islam (Studi Kasus Wanita Karir Di Desa Benda Kec. Sirampog Kab. Brebes) - Badriah Badriah; Chaula Luthfia; Qotrun Nida (Fakultas Hukum Universitas Sultan Ageng Tirtayasa, 2023)
Based on Islamic sharia teachings, a wife has obligations that must be carried out in the household, including obligations to husbands, obligations to children and also obligations to parents. The entry of wives into the world of work provides various changes in roles in carrying out their obligations and rights that have been agreed upon by husband and wife in the marriage system and this can be a source of problems for husbands and wives in the continuity of their marriage. A married couple in Benda village, Sirampog District, Brebes Regency is an example of a family that has experienced a shift in roles due to the participation of wives in making a living. This research is a field research using a sociological normative approach. This approach is intended to know and provide an overview of the fulfillment of the rights and obligations of husband and wife in the family of career women. From the results of the study, informants shared domistic work roles with husbands, 25% of informants acted as career women with conditions and limitations of domestic work had been carried out, 25% of informants performed the role of career women with full flexibility without being burdened by domestic work. This is in accordance with the Marriage Law on the rights and obligations of husband and wife in chapter V articles 30 to 34. Double burden wife who acts as a career woman who has an impact on domestic affairs. Where domestic affairs then become a shared responsibility with the man/husband, this is also as implicitly shown in QS An-Nisa: 32 and QS. Al-Baqarah [2]: 228.